2003
DOI: 10.1038/sj.tpj.6500195
|View full text |Cite
|
Sign up to set email alerts
|

Haplotypes of the cholesteryl ester transfer protein gene predict lipid-modifying response to statin therapy

Abstract: Cholesteryl ester transfer protein (CETP) plays a central role in high-density lipoprotein (HDL) metabolism. Single nucleotide polymorphisms (SNPs) and haplotypes in the CETP gene were determined in 98 patients with untreated dyslipidemias and analyzed for associations with plasma CETP and plasma lipids before and during statin treatment. Individual CETP SNPs and haplotypes were both significantly associated with CETP enzyme mass and activity. However, only certain CETP haplotypes, but not individual SNPs, sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 54 publications
2
22
0
Order By: Relevance
“…In addition, when age, race, smoking status, and body mass index are added to the model, the combination of these parameters accounts for 24% of the variation in LDL-C response, 29% of the variation in apoB response, and 8% of the variation in triglyceride, with HMGCRv_1 gene expression the most significant predictor of response in all 3. Because previous studies of genetic variation associated with statin response have explained Ͻ2% to 7.5% of the variation in LDL-C and HDL-C, 8,27 our findings point to a pathway that has much more substantial impact than previously identified SNPs. This finding is the first to establish a substantial contribution of a biological process to variation in statin efficacy.…”
Section: Discussionmentioning
confidence: 52%
“…In addition, when age, race, smoking status, and body mass index are added to the model, the combination of these parameters accounts for 24% of the variation in LDL-C response, 29% of the variation in apoB response, and 8% of the variation in triglyceride, with HMGCRv_1 gene expression the most significant predictor of response in all 3. Because previous studies of genetic variation associated with statin response have explained Ͻ2% to 7.5% of the variation in LDL-C and HDL-C, 8,27 our findings point to a pathway that has much more substantial impact than previously identified SNPs. This finding is the first to establish a substantial contribution of a biological process to variation in statin efficacy.…”
Section: Discussionmentioning
confidence: 52%
“…Theoretically, a haplotype has a higher level of heterozygosity than single SNP and the association study based on the haplotype may have an increased power to detect disease associations (10-12) compared with SNP-based analysis, which has been evidenced in association studies between the haplotypes of the cholesteryl ester transfer protein gene and lipid-modifying response to statin therapy (13) and between the haplotypes of h 2 -adrenergic receptor gene and receptor expression and in vivo responsiveness (14). Recently, four haplotype-tagging SNPs (htSNP), including Arg 194 Trp, Arg 280 His, Arg 399 Gln, and Gln 632 Gln, have been reconstructed based on the resequencing data of the XRCC1 gene from the NIH DNA Polymorphism Discovery Resource (15) and five common (>5%) haplotypes were inferred in this mixed population group.…”
Section: Introductionmentioning
confidence: 99%
“…In our case, the analyzed construct contained many mutated bases that could potentially affect the binding of more transcription factors and could, therefore, lead to thinner regulation of transcriptional promoter activity. Moreover, some authors have indicated that the unique interactions of multiple SNPs within a haplotype can affect the biological phenotype while single polymorphisms within the haplotype may have poor predictive power (Drysdale et al, 2000;Winkelmann et al, 2003).…”
Section: In Vitro Analysis Of the Leptin Promotermentioning
confidence: 99%